Early Childhood Education Learning in the Context of Modern Technology (A Study at RA Annahdliyah Cirebon) - Hafizudin, Hafizudin (Al-Banat: Journal of Early Childhood Islamic Education, 2025)
Background: Despite growing evidence supporting play-based learning for cognitive development, many early childhood education (ECE) institutions in Indonesia, particularly in semi-urban settings, still emphasize teacher-centered academic approaches. This creates tension between developmental appropriateness and academic pressure from parents and market expectations.Objective: This study aimed to explore the implementation of play-based learning and its effectiveness in enhancing cognitive skills of children aged 4–6 years at RA Nurul Iman Leuwimunding, Majalengka, and to identify contextual barriers and enabling factors.Method: A qualitative case study approach was employed, involving 160 classroom observation sessions, 43 in-depth interviews with stakeholders (teachers, parents, head of institution, and children), two focus group discussions, and document analysis conducted over six months. Data were analyzed using constant comparison and thematic analysis informed by grounded theory.Findings and Implications: Six major themes emerged: (1) significant tension between academic pressure and developmental appropriateness, with academic drills occupying 42% of learning time compared to 8% for structured play; (2) a substantial gap between teachers’ conceptual understanding of play-based learning and their technical competence to facilitate cognitive-focused play; (3) successful adaptation of play-based approaches in resource-constrained settings; (4) the critical role of teacher professional development; (5) low parental engagement in supportive play at home; and (6) the absence of systematic monitoring of cognitive development. These findings imply the need for targeted professional development, strategic parental engagement programs, curriculum integration frameworks, and systematic monitoring systems to optimize play-based learning implementation.Conclusion: While play-based learning offers substantial potential for enhancing early cognitive development, its effectiveness depends critically on addressing teacher knowledge gaps, strengthening institutional support, and aligning stakeholders in semi-urban ECE contexts.